Unsettling apologies : critical writings on apology from South Africa - Judge, Melanie; Smythe, Dee (Law, Society, Policy Ser., 2022)
Drawing on the histories of injustice, dispossession and violence in South Africa, this book examines the cultural, political and legal role and value of an apology.